Sex differences in hedonic judgement of odors in schizophrenia cases and healthy controls. (November 2018) - Walsh-Messinger, Julie; Wong, Philip S.; Antonius, Daniel; McMahon, Kevin; Opler, Lewis A.; Ramirez, Paul Michael; Malaspina, Dolores
Highlights: This study examined sex differences in olfactory hedonics in schizophrenia. Male schizophrenia cases and female controls rated pleasant odors as more unpleasant than male controls. Negative symptom severity was associated with hedonic ratings of pleasant and unpleasant odors. Positive symptom severity was associated with hedonic ratings of neutral odors. Correlations between depression and pleasantness ratings for neutral odors differed by sex. Abstract: The neurocircuitries subserving affective and olfactory processes overlap, are sexually dimorphic, and show disruptions in schizophrenia, suggesting their intersection may be a window on the core process producing psychosis. This study investigated diagnostic and sex differences in hedonic judgments of odors and smell identification in 26 schizophrenia cases and 27 healthy controls. Associations between olfaction measures and psychiatric symptoms were also examined. Cases and controls had similar identification accuracy of unpleasant odors, but cases were significantly less accurate in naming pleasant odors. In cases, greater negative symptom severity was related to abnormal hedonic judgments; specifically, higher pleasantness ratings for unpleasant odors and higher unpleasantness ratings for pleasant odors. Greater positive symptom severity was associated with lower pleasantness ratings for neutral odors. Regarding sex differences, male cases and female controls rated pleasant odors as significantly more unpleasant than male controls. Correlations between depression severity and pleasantness ratings of neutral odors were in opposite directions in male and female cases. These results suggest that a normal sexual dimorphism in the circuitry for hedonic odor judgments may interact with schizophrenia pathology, supporting the utility of olfactory hedonics as a sex-specific biomarker of this pathology.